HUBUNGAN ANTARA DISIPLIN DALAM BELAJAR DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD GUGUS ANGGREK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Irza Warda Fitria; Gustimal Witri; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The attitude of students' learning discipline at this time is very concerning. There are still many students who are notdisciplined in learning. This will certainly affect the knowledge and learning outcomes. The purpose of this study was to findout whether there is a relationship between discipline in learning with the results of mathematics learning in fifth gradeelementary SD Gugus Anggrek Kecamatan Benai Kabupaten Kuantan Singingi and to find out the level of significancebetween the discipline in learning and the results of mathematics learning in fifth grade SD Gugus Anggrek KecamatanBenai Kabupaten Kuantan Singingi. This type of research is quantitative research with a causal correlation research design.The number of samples in this study amounted to 80 students. The sampling technique is using saturated sample technique.Data collectiontechniques using observation, documentation,and questionnaires. Data analysis uses descriptive statistics andinferential statistics. The results of this study indicate that there is a relationship between discipline in learning with theresults of mathematics learning in fifth grade SD Gugus Anggrek Kecamatan Benai Kabupaten Kuantan Singingi. Therelationship between discipline in learning and learning outcomes of Mathematics is equal to 0.385 included in the lowcategory. The determinant coefficient is 14.82%, meaning that the discipline of learning contributes 14.82% to the results oflearning mathematics. And the remaining 85.18% is contributed by other factors outside the discipline of learning variables.